2016
DOI: 10.1038/ncomms13531
|View full text |Cite
|
Sign up to set email alerts
|

Spray printing of organic semiconducting single crystals

Abstract: Single-crystal semiconductors have been at the forefront of scientific interest for more than 70 years, serving as the backbone of electronic devices. Inorganic single crystals are typically grown from a melt using time-consuming and energy-intensive processes. Organic semiconductor single crystals, however, can be grown using solution-based methods at room temperature in air, opening up the possibility of large-scale production of inexpensive electronics targeting applications ranging from field-effect transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 31 publications
1
48
0
Order By: Relevance
“…From the SCLC theory, the charge‐carrier mobility in this sample has been estimated to be (4.0 ± 0.7) × 10 −2 cm 2 V s −1 (see Figure S4, Supporting Information). This is a relatively low value when compared to recently reported TIPS single crystals . We attribute this difference to two factors: (i) the high surface roughness of the PEN substrate (which has an Rms, Root Mean Square roughness, in the order of several nanometers), that hinders a full and homogeneous contact of the crystals with the electrodes, and (ii) the still unoptimized printing process, which is not yet able to deliver uniformly oriented crystals, or, very likely, to a combination of these factors.…”
Section: Summary Of the Various Step Heights Observed In The Afm Scanmentioning
confidence: 73%
See 1 more Smart Citation
“…From the SCLC theory, the charge‐carrier mobility in this sample has been estimated to be (4.0 ± 0.7) × 10 −2 cm 2 V s −1 (see Figure S4, Supporting Information). This is a relatively low value when compared to recently reported TIPS single crystals . We attribute this difference to two factors: (i) the high surface roughness of the PEN substrate (which has an Rms, Root Mean Square roughness, in the order of several nanometers), that hinders a full and homogeneous contact of the crystals with the electrodes, and (ii) the still unoptimized printing process, which is not yet able to deliver uniformly oriented crystals, or, very likely, to a combination of these factors.…”
Section: Summary Of the Various Step Heights Observed In The Afm Scanmentioning
confidence: 73%
“…On the other hand, attempts to detach the printed crystals from the substrate to submit them to traditional XRD invariably resolved in crystals cracking/breaking. Therefore, we turned to polarized optical microscopy, since it is known that this technique can discern between single and polycrystals, even in the specific case of TIPS‐pentacene . Due to the setup characteristics (optical transmission microscope), the crystals have been imaged together with the underlying PEN substrate, which was transparent enough to observe that the printed crystals are actually single ones.…”
Section: Summary Of the Various Step Heights Observed In The Afm Scanmentioning
confidence: 99%
“…Furan-based biopolymers have received considerable attention in recent years because of their great potential to replace petroleum-based plastics [11]. Organic Semiconductor Single Crystals [58,71,72] are also considered to be an important research topic, given they are "ideal candidates for the construction of high-performance optoelectronic devices/circuits" [55]. In this study, we reported the topochemical polymerization of a furan-based diacetylene (Furan-DA 1).…”
Section: Discussionmentioning
confidence: 99%
“…The 1D OSCCs are formed due to anisotropic growth in π–π stacking orientation, facilitating the carrier transport or photon propagation in the 1D crystals along the axial direction. So, besides the OFETs, 1D OSCCs have also exhibited great potential for laser and optical waveguide applications . 2D OSCCs are produced by the in‐plane growth of the crystals.…”
Section: Introductionmentioning
confidence: 99%